The first 10 years of the American Board of Vascular Medicine. (February 2015) - Gray, Bruce H; Jaff, Michael R; Slovut, David Paul; Bacharach, J Michael; Carman, Terry; Creager, Mark; Halperin, Jonathon; von Mering, Gregory; Kinlay, Scott
The American Board of Vascular Medicine (ABVM) was conceived through the Society for Vascular Medicine and this year will complete 10 years of certifying physicians who practice vascular medicine and endovascular medicine. The value of certification to our physicians, patients, and field cannot be understated. This paper reviews the highlights of the test development process, quality assurance measures, and management of these high stakes examinations.